Recepcja nauczania Jana Pawła II o zbawczym sensie cierpienia w kaznodziejstwie polskim - Bałabuch, Adam (Studia Pastoralne, 2026)
According to teaching of John Paul II looking at a reality of suffering in the perspective of a redemptive work of Jesus Christ is a vital moment which points at an essential correctness in presenting a sense of suffering. This is why it is around this view on the mystery of suffering a merit-related assessment of Polish preaching on the subject should be concentrated. Redemptive events are the basis for understanding a value of suffering which often touch human existence in a painful way. Thought of John Paul II is harmonious with homilies which try to explain the sense of suffering in the light of the mystery of redemption. A very positive element on preaching is showing a reality of suffering in the light of Christ’s victory that was won in resurrection. Among negative tendencies visible in the analysed homilies one should mention the fact that some preachers, looking for a sense of suffering in the light of faith, refer to the light that comes from the redemptive events only in a limited way, or show the value and meaning of the cross without their link to a soteriology. A serious weakness of many homilies is underlying the mystery of passion of Christ without its natural connection to the mystery of His resurrection. A certain group of authors cannot see a relation between the truth of a redemptive suffering and the truth of a primeval love of God for men.